The extent of Yemeni society's acceptance of the application of artificial intelligence in the field of dentistry: A case study in the city of Taiz - Abdulhameed, Ahmed Mohammed Mahmood; Sufyan, Amer Abdo Mohammed (Journal of medical and pharmaceutical sciences, 2025)
Artificial intelligence (AI) technologies in dentistry represent prominent technological innovations with the potential to revolutionize oral healthcare delivery by enhancing diagnostic accuracy and improving treatment efficiency through novel and effective methods.1 This study aimed to explore the acceptance of AI applications in dentistry within the Yemeni community, specifically in Taiz city, and to assess the level of awareness and understanding of this advanced technology. A descriptive analytical methodology was employed, utilizing a detailed questionnaire distributed to a random sample representing dentists, dental assistants, and dental patients. The results revealed that awareness of AI technologies and their applications in dentistry remains considerably limited, with a noticeable variation in opinions regarding the benefits and risks of this technology. The study identified cultural and social challenges impacting the implementation of AI in dentistry, such as concerns about the cost of new technology and fears of job displacement due to increased reliance on AI. Based on these findings, the study recommends the necessity of raising awareness and education about the benefits of AI, developing advanced training programs for dentists and practitioners, and improving healthcare infrastructure to facilitate the implementation of this technology and maximize its societal benefits.
Keywords: Artificial Intelligence; Dentistry; Community Acceptance; Technological Awareness; Social and Cultural Challenges; Healthcare Infrastructure; Technological Advancement